2012
DOI: 10.1186/1471-2334-12-86
|View full text |Cite
|
Sign up to set email alerts
|

The high comorbidity burden of the hepatitis C virus infected population in the United States

Abstract: BackgroundChronic hepatitis C (HCV) disease can be complicated with comorbid conditions that may impact treatment eligibility and outcomes. The aim of the study was to systematically review comorbidities and symptoms in an HCV infected population, specifically assessing comorbidities associated with HCV anti-viral treatment and disease, as well as comparing comorbidities between an HCV infected and uninfected control population.MethodsThis was a retrospective cohort study within a United States medical claims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
3
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 33 publications
7
72
3
6
Order By: Relevance
“…A small cross-sectional retrospective study investigating comorbidities associated with HCV from 1998 to 2007 found that HIV/AIDS, renal disease, diabetes, and obesity were more prevalent in patients with HCV compared with the U.S. population [27]. Higher comorbidity rates may reflect the selective age distribution of the HCV population, but there is also some recent evidence that comorbidity rates may be higher in the HCV population even after adjusting for age [17]. In our study, the potential increasing comorbidity rates may be related to the increasing average age of the underlying HCV population and have implications for increasing polypharmacy and complexity of DDI assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small cross-sectional retrospective study investigating comorbidities associated with HCV from 1998 to 2007 found that HIV/AIDS, renal disease, diabetes, and obesity were more prevalent in patients with HCV compared with the U.S. population [27]. Higher comorbidity rates may reflect the selective age distribution of the HCV population, but there is also some recent evidence that comorbidity rates may be higher in the HCV population even after adjusting for age [17]. In our study, the potential increasing comorbidity rates may be related to the increasing average age of the underlying HCV population and have implications for increasing polypharmacy and complexity of DDI assessment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, comorbidities that were reported previously as highly prevalent in chronic HCV patients or otherwise believed to be clinically relevant were identified for each 1-year cross-sectional cohort in either the inpatient or outpatient files using compiled ICD-9 code definitions from the medical literature (Appendix A) [17, 18]. Compensated cirrhosis was defined directly by ICD-9 code definition; advanced liver disease was a composite definition representing decompensated disease and included codes for ascites, spontaneous bacterial peritonitis, hepatic encephalopathy, portal hypertension, esophageal varices, hepatorenal syndrome, or hepatocellular carcinoma.…”
Section: Methodsmentioning
confidence: 99%
“…It is a leading cause of liver disease, cirrhosis, hepatocellular carcinoma, and liver transplantation (Lauer & Walker, 2001), and is associated with very high medical and psychiatric comorbidity (Butt et al, 2007; Louie et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Comorbidities, such as diabetes and obesity, are more common among patients with hepatitis C virus infection than in the general U.S. population, with as many as 25% of patients with hepatitis C virus infection at risk of comorbid disorders of lipid metabolism (2). Thus, patients with hepatitis C virus infection frequently receive concomitant treatments for hyperlipidemia, including the 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors atorvastatin and pravastatin.…”
mentioning
confidence: 99%